There are 700 residential lots available for development.
To solve this problem, we first need to convert the given land area from acres to square feet. One acre is equal to 43,560 square feet, so 175 acres is equal to 7,623,000 square feet.
Next, we need to subtract 25 percent of the land area from the total to get the area available for residential lots.
7,623,000 square feet x 0.75 = 5,717,250 square feet available for residential lots.
Finally, we divide the available area by the minimum required area per lot to get the total number of lots available:
5,717,250 square feet ÷ 7,500 square feet per lot = 7623/10 = 700 lots available for development.
Learn more about the Area of Land:
https://brainly.com/question/31218388
#SPJ4
if 2(x+10)=4x, what is x?
Answer:
x = 10
Step-by-step explanation:
First distribute the 2 into the parentheses
2x+20 = 4x
20 = 2x
x = 10
Show that if xn>0 for all nN, and lim (xn)=0, then lim(sqrt(xn)
If xn>0 for all nN, and lim (xn)=0, then lim(√(xn))=0
We know that the limit of a sequence is unique. Since lim(xn) = 0, we have that for every ε > 0, there exists an N ∈ ℕ such that for all n ≥ N, we have |xn - 0| < ε, which implies xn < ε. Now, consider the sequence √(xn). Since xn > 0 for all n ∈ ℕ, we can take the square root of both sides of the inequality xn < ε. This gives us:
√(xn) < √(ε).
Since ε > 0 can be arbitrarily small, it's clear that lim(√(xn)) = 0, as for every ε > 0, there exists an N such that for all n ≥ N, we have √(xn) < √(ε).
Given the conditions that xn > 0 for all n ∈ N and lim(xn) = 0, we have shown that lim(√(xn)) = 0.
To know more about limit, click here
https://brainly.com/question/12211820
#SPJ11
A marble rolls on a metal track from rest starting from a position x_(1)=3.4cm to x_(2)=-4.2cm during the time t_(1)=3.0s to t_(2)=6.1s. A. What is the average velocity of the marble? (2pts ) B. What is the Acceleration that the marble experiences? (2pts )
A. The average velocity of the marble can be calculated by dividing the change in position (x) by the change in time (t).
Average velocity = (x2 - x1) / (t2 - t1)
Substituting the given values:
Average velocity = (-4.2 cm - 3.4 cm) / (6.1 s - 3.0 s)
= -7.6 cm / 3.1 s
= -2.45 cm/s
Therefore, the average velocity of the marble is -2.45 cm/s.
B. The acceleration experienced by the marble can be determined by dividing the change in velocity (Δv) by the change in time (Δt). Since the initial velocity is zero (starting from rest), the change in velocity is equal to the final velocity (v) itself.
Acceleration = Δv / Δt
Substituting the given values:
Acceleration = (v - 0) / (t2 - t1)
= v / (6.1 s - 3.0 s)
= v / 3.1 s
Since the given information does not provide the final velocity (v), we cannot calculate the acceleration accurately.
The average velocity of the marble is -2.45 cm/s, indicating that the marble moves in the negative x direction. However, without the final velocity information, we cannot determine the exact acceleration experienced by the marble.
To know more about velocity follow the link:
https://brainly.com/question/32605616
#SPJ11
Which expression is equivalent to 2x ^ 2 - 2x + 77 ? (4x + 1.2) + (2x ^ 2 - 6x + 5) (x ^ 2 - 5x + 13) + (x ^ 2 + 3x - 6) (4x ^ 2 - 6x + 11) + (2x ^ 2 - 4x + 4) (5x ^ 2 - 8x + 120) + (- 3x ^ 2 + 10x - 13)
Answer:
None of the answers provided are equivalent
Step-by-step explanation:
To solve it would be best to simplify each of the expressions you have listed by combining like terms all the x^2 terms have been bolded, the x terms italicized, and the constant terms are underlined
(4x + 1.2) + (2x ^ 2 - 6x + 5) = 2x ^ 2 - 6x + 6.2
(x ^ 2 - 5x + 13) + (x ^ 2 + 3x - 6) = 2x^2 -2x +7
(4x ^ 2 - 6x + 11) + (2x ^ 2 - 4x + 4) = 6x^2 -10x +15
(5x ^ 2 - 8x + 120) + (- 3x ^ 2 + 10x - 13) = 2x^2 + 2x + 107
Assume that A is true, B is false, C is true, D is false What is
the truth value of this compound statement? (A V B) → [(C ∨ B) ↔
~D] Group of answer choices
If A is true, B is false, C is true and D is false, then the truth value of the compound statement (A V B) → [(C ∨ B) ↔~D] is True.
To determine the truth value of the compound statement, follow these steps:
The OR operator returns True if at least one of its operands is True. ∴ (C ∨ B) = True V False = True. The NOT operator returns True if its operand is False. ∴ ~D = ~ False= True. Since both sides of the biconditional operator must have the same truth value, we can evaluate each side separately and compare them:(C ∨ B) = True and ~D = True (since both operands are true). Therefore, (C ∨ B) ↔ ~D = True.The implication operator returns False only if its premise (the part before the arrow) is True and its conclusion (the part after the arrow) is False. Otherwise, it returns True. So, (A V B) is True because A is True. Also, [(C ∨ B) ↔ ~D] is True because both sides have the same truth value. Therefore, the whole expression is True.So, the truth value of the compound statement (A V B) → [(C ∨ B) ↔ ~D] when A is true, B is false, C is true, and D is false is True.
Learn more about compound statement:
brainly.com/question/28556870
#SPJ11
The standard length of a piece of cloth for a bridal gown is 3.25 meters. A customer selected 35 pcs of cloth for this purpose. A mean of 3.52 meters was obtained with a variance of 0.27 m2 . Are these pieces of cloth beyond the standard at 0.05 level of significance? Assume the lengths are approximately normally distributed
The pieces of cloth are beyond the standard at 0.05 level of significance.
We can use a one-sample t-test to determine if the mean length of the 35 pieces of cloth is significantly different from the standard length of 3.25 meters.
The null hypothesis is that the mean length of the cloth pieces is equal to the standard length:
H0: μ = 3.25
The alternative hypothesis is that the mean length of the cloth pieces is greater than the standard length:
Ha: μ > 3.25
We can calculate the test statistic as:
t = (x - μ) / (s / √n)
where x is the sample mean length, μ is the population mean length (3.25 meters), s is the sample standard deviation (0.52 meters), and n is the sample size (35).
Plugging in the values, we get:
t = (3.52 - 3.25) / (0.52 / √35) = 3.81
Using a t-table with 34 degrees of freedom (n-1), and a significance level of 0.05 (one-tailed test), the critical t-value is 1.690.
Since our calculated t-value (3.81) is greater than the critical t-value (1.690), we reject the null hypothesis and conclude that the mean length of the 35 pieces of cloth is significantly greater than the standard length at the 0.05 level of significance.
Know more about level of significance here:
https://brainly.com/question/30542688
#SPJ11
Find AB to the nearest tenth.
The length of the line segment AB to the nearest tenth as required to be determined is; 19.1cm.
What is the length of AB?It follows from the task content that it can be inferred that; AB = 2AD.
Since the diameter of the circle is 28cm; it follows that the radius of the circle is; 28/2 = 14cm.
Hence, from trigonometric ratios;
sin ¢ = AD / OA where OA = 14 and ¢ = 86/2 = 43°.
Consequently, AD = 14 sin 43°.
AB = 2 × 14 sin 43°.
AB = 19.1
Consequently, the length of AB is; 19.1.
Read more on length of chord;
https://brainly.com/question/12998698
#SPJ1
If m23 = 54°, find the measure of each missing angle.
Answer:
Holo nomelase ay pa la próxima
Need this asap if you help Tysm!!!
Answer:
B. -$0.75
Step-by-step explanation:
that is really very simple.
the value on day 1 (the begin) is $2.50.
the value on day 5 (the end of the week I assume) is $1.75.
so, the value changed by -$0.75 from $2.50 to $1.75.
yes, this is the sum of all little individual changes day by day. but there is no need to do these detailed calculations. at the end it is just
value end - value begin
Please show step by step how to do this (2-step) equation
3x + 6 = 21
Answer:
x = 5
Step-by-step explanation:
3x + 6 = 21
3x = 21 - 6
3x/3 = 15/3
x = 5
4 pairs of shoes cost $80. What is the cost of 7 pairs of shoes?
Answer:
560 $
Step-by-step explanation:
4 shoes is 80
so, we have to multiply
$140
Or
£140
You are American so its the first one
Solve the recursion using all three methods in any order you choose. Clearly label each solution as recursion tree, substitution, or Master Theorem. (15pt: 5 for each method): T(n)=2T(n/2)+23n
The solution of the given recurrence relation `T(n) = 2T(n/2) + 23n` using all three methods are:`T(n) = Θ(nlog2n)`
Given recursive relation is `T(n) = 2T(n/2) + 23n`.
We have to solve the above recursion using all three methods in any order we choose and label each solution as recursion tree, substitution, or Master Theorem.
Now, let's solve the above recursion using all three methods one by one:
1. Recursion Tree method:
To solve the above relation using recursion tree method, we will create a tree and the value of each level will be the sum of the values of all nodes present in that level or the sum of all previous levels + current level.
The tree will look like:
Therefore, the answer of the given recurrence relation `T(n) = 2T(n/2) + 23n` using the recursion tree method is:
`T(n) = Θ(nlog2n)`
2. Substitution method:
To solve the above recurrence relation using the substitution method, we can assume a solution and prove it by the Mathematical induction method.
Let `T(n) = 2T(n/2) + 23n`
Then, `T(n/2) = 2T(n/4) + 23n/2`
Also, `T(n/4) = 2T(n/8) + 23n/4`
Therefore, `T(n) = 2(2T(n/4) + 23n/2) + 23n`Or, `T(n) = 2²T(n/2²) + 23n(1 + 2)`
In general, we have `T(n) = 2kT(n/2k) + 23n(1 + 2 + ... + 2k-1)`
When `n/2k = 1`Or, `k = log2n`
Therefore, `T(n) = 2log2nT(1) + 23n(1 + 2 + ... + 2log2n-1)`Or, `T(n) = 2log2nT(1) + 23n(2log2n - 1)`
As `T(1) = 1`
Therefore, `T(n) = Θ(nlog2n)`
Hence, the answer of the given recurrence relation `T(n) = 2T(n/2) + 23n` using the substitution method is:
`T(n) = Θ(nlog2n)`
3. Master Theorem method:
To solve the above recurrence relation using the Master theorem, we have to compare the function `nlogba` with the function `f(n)`.
Here, `a = 2`, `b = 2`, and `f(n) = 23n`.
As per the Master theorem:
`If f(n) = Θ(nlogba),
then T(n) = Θ(nlogba log2n)` `
= Θ(nlog2n)` if
`f(n) = 23n
= Θ(nlog2n)`
Therefore, the solution of the given recurrence relation `T(n) = 2T(n/2) + 23n` using the Master theorem is:
`T(n) = Θ(nlog2n)`
Hence, the solution of the given recurrence relation `T(n) = 2T(n/2) + 23n` using all three methods are:`T(n) = Θ(nlog2n)`
Learn more about Master Theorem from the given link :
https://brainly.com/question/31033429
#SPJ11
Use the Distributive Property to rewrite each expression. Then evaluate.
7(6-4)
Answer:
14
Step-by-step explanation:
PEMDAS:
P: Parentheses
E: Exponents
M: Multiplication
D: Division
A: Addition
S: Subtraction
Step 1:
7 ( 6 - 4 ) Equation
Step 2:
7 ( 2 ) Subtract
Answer:
14
Hope This Helps :)
the solution of -6+a=22
Answer:
a=28
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
a−6=22
Step 2: Add 6 to both sides.
a−6+6=22+6
a=28
WILL MARK BRAINLIEST!!! Your friend states that for functions of the form y = a sin bx and y = a cos bx, the values of a and b affect the x-intercepts of the graph of the function. Is your friend correct? Explain
Answer:
The sine function won't be affected, but the consine function will.Step-by-step explanation:
First of all, remember that \(sin(0)=0\) and \(cos(0)=1\). As you can see, the sine function won't be affect by \(a\), because its value is null.
However, the x-intercept of the cosine function depends on the \(a\) value, because the function is equal to the unit.
On the other hand, the variable \(b\) won't affect any function, because it would be always zero.
Therefore, the sine function won't be affected, but the consine function will.
slove for x
2(x+3)=x-4
Answer:
answer would be -10 for x
Answer:
your answer is x= -10
Step-by-step explanation:
i cant put in the image from the calculator but i hope this still helps
if im wrong pls let me know
but if im right may i please be marked braniliest
Solve and show your work or explain.
\(x-\sqrt{2x-5}=5\)
Answer:
\(x= 6+ \sqrt {6}\)
Step-by-step explanation:
\(-\sqrt {2x-5}+x=5\\-\sqrt {2x-5}=-x+5\\\\\frac {-\sqrt {2x-5}}{-1} = \frac {-x+5}{-1}\\\\\sqrt {2x-5}=x-5\\2x-5=(x-5)^2\\2x-5=x^2-10x+25\\2x-5-(x^2-10x+25)=x^2-10x+25-(x^2-10x+25)\\-x^2+12x-30=0\\\\x=\frac {-12(+/-)\sqrt {12^2-4(-1)(-30)}}{2(-1)}\\\\x=6+\sqrt {6}\)
Congratulatiohs! You just got your first job. The manager says your starting yearly salary will be $20,800. The
manager will give you the same amount of money as a raise each year. In 5 years, you will make $24,128.
How much will you make in ten years?
Answer:
120,640
Step-by-step explanation:
Which equation does not represent direct variation?
y = 1/3x
y + 3x= -2x
y = 4x + 1
6x - y = 0
Answer:
the first one ithink
Step-by-step explanation:
;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;;
Answer:
Step-by-step explanation:
helppp ……………
……………………………..
Answer: It's D
Step-by-step explanation:
Because you have to square root it and look back at the answer, so the number is 19, and look back at the line where is 19? That's your answer.
Write an equation for the following, then solve. Show your work.
If a number is subtracted from its square, the result is 90. Find the number(s).
Answer:
x = -9, 10
Step-by-step explanation:
\(x^2 - x = 90\\\)
Solve this as a quadratic equation, so subtract 90 from both sides:
\(x^2-x-90=0\)
Factoring:
\((x+9)(x-10) = 0\)
This means that:
\(x + 9 = 0\\\\x=-9\\or\\x - 10 = 0\\x = 10\)
x can be -9 or 10.
Let X denote the number of exam questions a student got correct by guessing the answer to each question on a multiple choice exam consisting of 10 questions, each with 3 possible answers O binomial O not binomial
The scenario described is binomial since the following conditions are met:
- The exam consists of a fixed number of 10 questions
- Each question has only 3 possible answers, making each guess a Bernoulli trial
- The probability of guessing correctly for each question is constant and independent of the other questions
Therefore, X, the number of exam questions a student got correct by guessing, follows a binomial distribution.
The situation described is an example of a binomial experiment or not. Let's analyze the given information:
1. There are a fixed number of trials (10 exam questions).
2. Each trial has two possible outcomes: correct or incorrect answer.
3. The probability of a correct answer is the same for each question (1/3, as there are 3 possible answers).
4. The trials are independent, meaning guessing the answer to one question doesn't affect the others.
Given these conditions, the situation is indeed a binomial experiment. So, X, which denotes the number of exam questions a student got correct by guessing, follows a binomial distribution.
Your answer: X is binomial.
Learn more about binomial distribution here: brainly.com/question/14565246
#SPJ11
15a + 9b 2a? - 4a + 6 - 9b
15a 4a_2a2 – 96 - 96 + 6
9a + Ob + 6
Is it true or false?
NONONONONONONONONONONONO
Alex knits hats and scarves to sell at a craft market. He can make at most 20 hats and 30 scarves, but no more than 40 items altogether, in time for the market.
Write and graph a system of inequalities that shows the possible numbers of hats and scarves Alex can bring to the craft market if he wants to bring at least 25 items. Identify three (3) possible combinations, and say which he should
choose.
The three (3) possible combinations are
hats = 10, scarves = 30hats = 10, scarves = 20hats = 20, scarves = 20Alex should 20 hats and 20 scarves
How to find the possible combinations Alex can bring to the marketLet the number of scarves be x and y be the number of hats
He can make at most 20 hats and 30 scarves, but no more than 40 items altogether
x ≤ 20
y ≤ 30
x + y ≤ 40 (in time of market)
x + y ≥ 25
The possible combinations are
1 ⇒ x = 10, y = 302 ⇒ x = 10, y = 203 ⇒ x = 20, y = 20He should choose the third option x = 20, y = 20 this allows him to take more products to the show
Learn more about inequality graph at:
https://brainly.com/question/11234618
#SPJ1
A coin is flipped 10 times where each flip comes up either heads or tails. How many possible outcomes a) are there in total
The answer is that there are 2¹⁰ (or 1024) possible outcomes in total.
When a coin is flipped 10 times, each flip has 2 possible outcomes: heads or tails. To find the total number of possible outcomes, you can use the formula for calculating the number of outcomes in an experiment with independent events:
Total outcomes = (Number of outcomes for each event)ⁿ (n=Number of events)
This is because each flip has two possible outcomes (heads or tails), and since there are 10 flips, we need to multiply 2 by itself 10 times (2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 = 1024).
Total outcomes = 2¹⁰ = 1,024
To know more about possible outcomes visit
brainly.com/question/27292589
#SPJ11
What is an example of a linear function table?.
An example of a linear function table is y=3x
A linear function is used to relate an independent variable and a dependent variable by introducing a rate of change(function) of which the independent variable is equated to find the dependent variable. Linear functions are those whose graph is a straight line. The following is the form of a linear function. a + bx = y = f(x). One independent variable and one dependent variable make up a linear function. X and Y are the independent and dependent variables, respectively.
for example:
y=3x hence is the dependent variable as it depends on the change of x and 3 is the rate of change which is a constant and is determined by the division of the values of y/x hence to make a table of y over x of which y is determined by the rate of change the unrelated variable x, 3.
Read more about linear function tables at:
https://brainly.com/question/25173046
#SPJ4
Mrs. Shelly paid $3 for 6 muffins and Mrs. Kloske paid $9 for 18 muffins. How much did
Mrs. Smith pay for 30 muffins?
Explain your answer
a) $3
b) $10
c) $15
d) $30
5 in
Area
6 in
7 in
10 in
15 in
HELP I NEED TO FIND AREA
Answer:
84in
Step-by-step explanation:
10 times 5 = 50 (top half)
7 times 4 = 28 (bottom half)
3 times 4 = 12 / 2= 6 (triagle)
A Right triangle has one acute angle of 43. what is the measure of the other acute angle
90 + 43 + x = 180
By Euclidean geometry, the measure of the missing angle, the other acute angle, of the right triangle is equal to 47°.
How to find the measure of the measing angle of the right triangleRight triangles are triangles of which one of its angles is a right angle and the other two angles are acute angles. According to the statement, the measure of an acute angle of the right triangle is equal to 43°.
By Euclidean geometry, the sum of the internal angles in any triangle equals a measure of 180°. Then, the measure of the missing angle is:
90° + α + β = 180°
If we know that α = 43°, then the value of β is:
α + β = 90°
43° + β = 90°
β = 47°
The measure of the missing angle is equal to 47°.
To learn more on right triangles: https://brainly.com/question/2869318
#SPJ1
7. Roberta and Eugene were trying to work out how
much charge there was stored in different electric
toothbrush batteries. They measured the current
flowing into toothbrush when it was switched on
and timed how long it took to run the batteries
down. The toothbrush required two batteries.
They repeated their experiment twice.
(Results in picture attached)
a) Circle the anomalous result in the table.
b) Calculate the mean average for each brand of
battery.
c) Calculate the amount of charge stored by each
brand of battery.
d) How would you present the results of this
experiment? Justify your answer.
Please help I have a test tmrw
a) The anomalous result in the table is the Durablast battery in the second trial, which recorded a time taken of 768 seconds.
b) The mean averages for each brand of battery are 955.33, 852 and 908 seconds.
c) the amount of charge stored by each brand of battery is 1098.6 coulombs, 1065 coulombs and 1089.6 coulombs.
d) The results of this experiment can be presented in a table format, showing the current flowing, the mean time taken, and the amount of charge stored for each brand of battery.
What is anomalous result?It is an unexpected or unusual outcome that does not agree with the expected or accepted outcome. It may be a result of a mistake, an anomaly in the data, or a misinterpretation of the data.
a) The anomalous result in the table is the Durablast battery in the second trial, which recorded a time taken of 768 seconds.
b) The mean averages for each brand of battery are:
Longalast: 955.33 seconds
Durablast: 852 seconds
Morelife: 908 seconds
c) The amount of charge stored by each brand of battery can be calculated by multiplying the current flowing into the toothbrush (amps) by the mean time taken (seconds) for each battery:
Longalast: 1.15 amps x 955.33 seconds = 1098.6 coulombs
Durablast: 1.25 amps x 852 seconds = 1065 coulombs
Morelife: 1.20 amps x 908 seconds = 1089.6 coulombs
d) The results of this experiment can be presented in a table format, showing the current flowing, the mean time taken, and the amount of charge stored for each brand of battery. This would allow the reader to easily compare the performance of each battery, as well as to identify any anomalous results.
For more questions related to experiment
https://brainly.com/question/25677592
#SPJ1